289 Comparison of ACR 1982/1997 and EULAR/ACR classification criteria for systemic lupus erythematosus in two multiethnic cohorts. (April 2019) - Pons-Estel, Guillermo J; Ugarte-Gil, Manuel F; Harvey, Guillermina B; Wojdyla, Daniel; Griffin, Russell; Saurit, Verónica; Soriano, Enrique; Bonfa, Eloisa; Massardo, Loreto; Cardiel, Mario H; Vila, Luis M; Alarcón, Graciela S; et al.
Abstract : Background: Classifying patients as having systemic lupus erythematosus (SLE) is critical for clinical trials and observational studies; although not designed for this purpose, criteria are also frequently used in clinical practice for early diagnosis. The SLICC 2012 criteria are more sensitive but less specific than the 1982/1997 ACR criteria. The refined 2018 EULAR/ACR criteria differ from the other two sets as they require a positive ANA as the entry point; in addition, the clinical manifestations are clustered into weighted domains with the goal of maximizing the likelihood of an accurate classification of SLE, particularly of early disease. The objective of the present study was to identify the distinct items of the clinical and immunological domains of the EULAR/ACR SLE classification criteria that differ in the time to criteria fulfillment when compared to the 1982/1997 ACR criteria in two multiethnic lupus cohorts. Methods: Patients from two multiethnic, multicenter cohorts, one from the US and the other from Latin America were included. For these analyses, EULAR/ACR items were evaluated to determine which clinical manifestations and/or laboratory parameters could be of help to achieve an earlier classification of patients. Categorical variables were compared using Chi-square or modified Fisher exact tests, as appropriate. The statistical analyses were performed using SAS software version 9.4. Results: Five-hundred and fifty-eight patients out of 640 from the US cohort and 956 out of 1047 from the Latin America cohort were included. Only 41 (7.3%) and 71 (7.4%) of patients achieved the 2018 EULAR/ACR criteria earlier in the US and Latin American cohorts, respectively. In turn, about one third of the patients in both cohorts achieved them later. Patients who accrued the 2018 EULAR/ACR earlier were more likely to have high anti-dsDNA titers and later earlier classification less likely to have mucocutaneous and joint manifestations; these data are depicted in table 1 . Conclusions: When both cohorts were taken it into account, those patients who achieved the 2018 EULAR/ACR criteria earlier had a lower frequency of milder manifestations (like mucocutaneous and articular) and tend to have a higher frequency of anti-dsDNA antibodies, suggesting these criteria could be more useful in subsets of patients with more severe disease. Funding Source(s): None